Dynamic Compressive Mechanical Properties of Rock-like Material with Bedding Planes Subject to Different Impact Loads - Xu, Xin; Jing, Hongwen; Yin, Qian; Wu, Jiangyu; Guzev, Mikhail Aleksandrovich; Jin, Jiawan (KSCE journal of civil engineering, 2024)
To explore the dynamic mechanical response of layered rocks under different impact pressures, dynamic impact experiments were performed on five sets of layered rock-like specimens at different dips with a splitting Hopkinson compression bar. The effects of impact pressure on the compressive properties of layered rocks are researched. The fracture patterns are also discussed regarding fragmentation morphology, fractal characteristics, and energy dissipation. The findings suggest that the dynamic compressive strength shows the “U” shape variation with the dip angle θ , firstly declining and then enlarging. The dynamic compressive strength grows with increased impact pressure at different dip angles. The dynamic compressive strength of the layered rock at different dip angles increased the fastest with the change of impact pressure from 0.2 MPa to 0.3 MPa. The fractal dimension D tends to enlarge with increasing impact load. There is a highly linear relationship between them. The D of the sample fragments increases slower as the θ increases. In general, the absorbed energy declines first and then enlarges. With the higher impact pressure, the percentage of the total absorbed energy increases for each θ , besides the energy gains. The broken effect of a high dip angle specimen is better when crushing rock at low impact pressure. And when that is high, it is easy to cut the surrounding rock vertically or parallel to the layer direction.